Study on Nanofibrillated Cellulose Preparation from Paper Mill Sludge by Sulphuric Acid Hydrolysis with Added Hydrogen Peroxide - Le, Quang Dien; Nguyen, The Sang; Nguyen, Thanh Long (Old Journal, 2019)
The fiber-containing sludge from treatment of paper mill effluents was used for preparation of nanofibrillated cellulose by multi-stage process. Firstly, the sludge was treated by hydrochloric acid solution and washed for recovery of cellulose. Secondly, as-recovered cellulosic pulp was treated by mixture of sulfuric acid 0.25% and added hydrogen peroxide 0.1% at 140°C for 2 hours. Cellulose pulp then was treated by solution of sodium hydroxide and hydrogen peroxide followed refining. The characteristics of nanofibrillated cellulose with fiber diameter less than 100 nm were determined by SEM, FTIR and XRD. The new method of nanocellulose preparation can be developed for production of value-added products from paper mill solid waste.